(untitled) (Research Journal of Mathematics & Technology, 2022)
We extend the locus problems discussed in [9], [10] and [12], for a quadric surface when the fixed point is at an infinity. This paper will benefit those students who have backgrounds in Linear Algebra and Multivariable Calculus. As we shall see that the transformation from a quadric surface to its locus surface Δ is a linear transformation. Consequently, how the eigenvectors are related to the position of the fixed point at an infinity will be discussed.